2014
DOI: 10.3390/molecules19033628
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Probiotics in Water Extractable Arabinoxylan Gels: Rheological and Microstructural Characterization

Abstract: Due to their porous structure, aqueous environment and dietary fiber nature arabinoxylan (AX) gels could have potential applications for colon-specific therapeutic molecule delivery. In addition, prebiotic and health related effects of AX have been previously demonstrated. It has been also reported that cross-linked AX can be degraded by bacteria from the intestinal microbiota. However, AX gels have not been abundantly studied as carrier systems and there is no information available concerning their capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Higher cell dimensions were reported in lyophilized AX gels (>200 μm) [17,19], and this difference could be related to the method used to freeze the gels before lyophilization. In the present study AX gels were frozen by immersion in liquid nitrogen (fast congelation), while previous studies [17,19] reported AX gel congelation at -20°C for several hours (slow congelation).…”
Section: Gelation Of Arabinoxylans Frommentioning
confidence: 99%
See 3 more Smart Citations
“…Higher cell dimensions were reported in lyophilized AX gels (>200 μm) [17,19], and this difference could be related to the method used to freeze the gels before lyophilization. In the present study AX gels were frozen by immersion in liquid nitrogen (fast congelation), while previous studies [17,19] reported AX gel congelation at -20°C for several hours (slow congelation).…”
Section: Gelation Of Arabinoxylans Frommentioning
confidence: 99%
“…This behavior reflects an initial formation of covalent linkages between FA of adjacent AX molecules producing a three-dimensional network [19]. At the end of gelation, G' and G" were 78 and 13 Pa for AX1, respectively, while for AX2 they were 32 Pa and 8 Pa for G' and G", respectively (Table 1).…”
Section: Rheological and Structural Characteristics Of Ax Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stability of the AX gels to changes in temperature, pH, and ionic strength offers an advantage for the industrial applications of this polysaccharide. A previous study has demonstrated that AX gels can be used for the entrapment of probiotics [10,11]. However, that investigation used water extractable AX from wheat flour as a model molecule due the less complex structure of this polysaccharide in comparison to water un-extractable AX from cereal brans.…”
Section: Introductionmentioning
confidence: 99%